The professional teacher : the preparation and nurturance of the reflective practitioner - Norlander-Case, Kay A.; Reagan, Timothy G.; Case, Charles W. (San Francisco : Jossey-Bass, 1999)
From the AgAnda for Education in a Democracy SeriesSponsored by the National Network for Educational Renewal"This book is comprehensive in its account of what goes into the substance and process of preparing the professional educator, from selection to induction into teaching
Includes bibliographical references
Keywords: Teachers -- Training of -- United States; Teachers -- In-service training -- United States; Action research in education -- United States